إسهامات العلماء الأندلسيين في نقل الموروث الحضاري البصري إلى الأندلس (172-366هـ/788-976م) - Abdul-Kareem Sadiq Alalwan, Assist. Prof. Dr. Atheer; Awad Yasser Al-Ameri , Assist .Prof. Dr. Thikra (Basra studies journal, 2026)
The history of al-Andalus witnessed the emergence of many scholars who played a significant role in transmitting the Basran cultural heritage to al-Andalus. Biographical sources provide us with the names of those scholars who traveled to the city of Basra in pursuit of knowledge, where they met its most distinguished scholars and teachers—jurists, hadith scholars, linguists, litterateurs, and physicians—and benefited from their knowledge, studying under their guidance. Some of these journeys extended over long periods of time, which helped them become acquainted with many of the prevailing customs, traditions, and social norms there. This led to their integration into Basran society and direct interaction with its inhabitants, allowing these customs to blend with their own social dispositions and become part of their lives and practices. Upon their return to al-Andalus, they transmitted to their people all that they had learned and acquired, including knowledge, scholarly works, customs, traditions, as well as their recorded observations and descriptions of general conditions and events that took place in Basra during their stay.